Sex-specific energy expenditure during the Alaska mountain wilderness ski classic; insights from an Arctic winter expedition - Coker, Melynda S.; Ravelli, Michelle N.; Shriver, Timothy C.; Schoeller, Dale A.; Slivka, Dustin R.; Ruby, Brent C.; Coker, Robert H. (Frontiers in Physiology, 2025)
PurposeThe Alaska Mountain Wilderness Ski Classic (AMWSC) is a self-supported and self-oriented winter expedition that occurs in the remote North American Brooks Range, ∼200 km north of the Arctic Circle. Few investigations have evaluated sex-specific physiological responses under extreme cold and isolated circumstances. Our study examined sex-specific differences in total energy expenditure (TEE), water turnover (WT), and changes in body composition during the expedition.MethodsTwenty adult participants (8 females, age: 41 ± 6 years, body mass index: 22.8 ± 1.9 kg/m2 and 12 males, age: 38 ± 4 years, body mass index: 22.7 ± 1.6 kg/m2) enrolled in and completed the study. TEE and WT were examined during the expedition using the doubly labeled water (DLW) method. Body composition was measured using multi-frequency bioelectrical impedance.ResultsThe duration of the expedition was similar in females (8.1 ± 1.6 days) and males (7.5 ± 0.9 days). Absolute rates of TEE were lower in females (20.8 ± 4.7 MJ/day) compared to males (31.1 ± 7.5 MJ/day). However, when expressed relative to fat free mass (FFM), rates of TEE were similar in females (0.42 ± 0.07 MJ/FFM/day) and males (0.45 ± 0.10 MJ/FFM/day). TEE/body mass plus pack weight (i.e., total load carriage) was lower in females compared to males. WT was reduced compared to previous reports of athletes exercising in thermoneutral and hot environments.ConclusionAbsolute rates of TEE were lower in females compared to males, but there was no difference when TEE was expressed relative to fat free mass. Estimates of TEE/total load carriage were lower in females than males, modestly suggesting greater functional efficiency in females during this expedition. Compared to other ultra-endurance events in warm environments, WT may have been reduced by lack of water availability, self-selected reductions in exercise intensity, and limited sweat loss.